IMPLEMENTASI KEBIJAKAN SISTEM FINGER PRINT PASIEN KHUSUS RAWAT JALAN BPJS KESEHATAN DI RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - Sukma Mahadini, Anisa; Larasati Setianingsih, Endang; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2024)
BPJS Kesehatan in managing health insurance program has faced losses due to misuse (fraud), including manipulation of bills by hospitals and falsification of cards by participants. To address these issues, BPJS Kesehatan developed an innovation by implementing a fingerprint system policy. The goal of this fingerprint system policy is to reduce fraud and ensure that health services are provided only to eligible participants. This study aims to analyze the implementation of the fingerprint system policy for outpatient BPJS Kesehatan based on Presidential Regulation Number 82 of 2018 concerning Health Insurance at PKU Muhammadiyah Gombong Hospital and to analyze the supporting and hindering factors in implementing this fingerprint system policy at PKU Muhammadiyah Gombong Hospital. The research method used is descriptive with a qualitative approach. The sampling technique for informants in this study is purposive sampling, with data collection methods including interviews, observations, and documentation. Data were analyzed using ATLAS.ti software. The study assesses the assurance of health service rights, the certainty of health service claims, and the effectiveness and efficiency of patient services. The results of this study indicate a lack of procedural information guidelines for the fingerprint system policy, inaccuracies by staff, limited outreach for socialization, and a decline in the performance of fingerprint recording devices. Recommendations from the study suggest that PKU Muhammadiyah Gombong Hospital should commit more to implementing the fingerprint system policy for outpatient BPJS Kesehatan and expand socialization efforts in collaboration with BPJS Kesehatan and community health centers (Puskesmas) to ensure effective policy execution.